2021
DOI: 10.1177/20416695211017564
|View full text |Cite
|
Sign up to set email alerts
|

Eye Placement Bias Is Remarkably Robust

Abstract: When drawing faces, people show a systematic bias of placing the eyes higher up the head than they are placed in reality. This study investigated the development of this phenomenon while removing the potential confound of drawing ability. Participants ( N = 124) in three age groups (3–5 yo, 10–11 yo, and adults) reconstructed two foam faces: one from observation and one from memory. The high eye placement bias was remarkably robust with mean eye placement in every condition significantly higher than the origin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Simpler versions of such a production task have also been used with developmental populations to estimate children's changing configural template for face detection and recognition. Both Balas et al (2023) and Smith et al (2021) found evidence of this bias in childhood, with younger children making especially large errors in eye height when producing images, but Balas et al additionally report that children in the target age range reliably recognized that faces with more canonical feature placement were better examples of typical face images. With regard to face recognition (rather than the overall face-ness of face portraits), production tasks also provide unique insights.…”
Section: Introductionmentioning
confidence: 99%
“…Simpler versions of such a production task have also been used with developmental populations to estimate children's changing configural template for face detection and recognition. Both Balas et al (2023) and Smith et al (2021) found evidence of this bias in childhood, with younger children making especially large errors in eye height when producing images, but Balas et al additionally report that children in the target age range reliably recognized that faces with more canonical feature placement were better examples of typical face images. With regard to face recognition (rather than the overall face-ness of face portraits), production tasks also provide unique insights.…”
Section: Introductionmentioning
confidence: 99%